The Sacrament of Reconciliation and Ethical Formation of the Catholic youth in Higher Education at Assumption Cathedral, Archdiocese of Bangkok - Tusamran, Somsak; Saengthien, Rev.Dr.Pichet; Chaiyadej, Rev.Chedtha; Prasootsaengchan, Asst.Prof.Dr. Laddawan (Saengtham College Journal, 2022)
This Mixed Methods Research aimed to study: 1) the state of the reconciliation of Catholic youth at Assumption Cathedral and 2) the result of the reconciliation in nourishing the ethical formation of the Catholic youth life at Assumption Cathedral, Archdiocese of Bangkok. The informants are the Catholic youth of Assumption Cathedral Archdiocese of Bangkok who are studying for university degrees by use to convenience selection. The research instruments are the questionnaires for the Catholic youth 30 persons, and a semi-structured interview with the 10 Catholic youth. The statistics for data analysis are frequency value, percentage and the data analysis from the interview. The result of this research reveal 1. the state of the reconciliation of the informants the Catholic youth at Assumption Cathedral, confess their sins 1-2 times a month. The others don’t confess their sins because they are late for confession time and can’t take part in the confession ceremony. The informants give priority and importance to the sacrament of reconciliation. This time of reconciliation with God and the Church will heal their contrite hearts and convert from their sins. After the confession of their sins, they feel content and closer to God. They try to sin no more. 2. the confession helps the Catholic youth of Assumption Cathedral to nourish their ethical life. Confession helps them to receive the grace of God, reconcile with Him, be healed in their contrite hearts, reminded of their sins and converts their heart to try to sin no more. Therefore Confession, penitence and sacrifice nourish their ethical life change their lives and bear more fruit in their families and society. It helps develop their life of love, mercy, honesty, patience, sacrifice, and forgiveness. It improves relationships and decreases conflict in the family; it is also good for society as it is a constant reminder of the need for reconciliation and the avoidance of sin, Create a good friendship with each other in community.